Overcoming barriers to promotion for women and underrepresented in medicine faculty in academic emergency medicine. Issue 6 (21st December 2021) - Oh, Laura; Linden, Judith A.; Zeidan, Amy; Salhi, Bisan; Lema, Penelope C.; Pierce, Ava E.; Greene, Andrea L.; Werner, Sandra L.; Heron, Sheryl L.; Lall,, Michelle D.; Finnell, John T.; Franks, Nicole; et al.
Abstract: Equity in the promotion of women and underrepresented minorities (URiM) is essential for the advancement of academic emergency medicine and the specialty as a whole. Forward‐thinking healthcare organizations can best position themselves to optimally care for an increasingly diverse patient population and mentor trainees by championing increased diversity in senior faculty ranks, leadership, and governance roles. This article explores several potential solutions to addressing inequities that hinder the advancement of women and URiM faculty. It is intended to complement the recently approved American College of Emergency Physicians (ACEP) policy statement aimed at overcoming barriers to promotion of women and URiM faculty in academic emergency medicine. This policy statement was jointly released and supported by the Society for Academic Emergency Medicine (SAEM), American Academy of Emergency Medicine (AAEM), and the Association of Academic Chairs of Emergency Medicine (AACEM).